2022
DOI: 10.33093/jclc.2022.2.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Netflix Binge-watching Behaviour among University Students during Movement Control Orde

Abstract: Streaming media like Netflix has become a mainstream trend for people to have fun and relax during the Covid-19 pandemic, and numerous studies found that college students and millennials account for a large group who binge-watch television programmes. Hence, understanding university students’ motive for binge-watching is timely, especially during the Covid-19 lockdown period, when there is a lack of studies on this phenomenon. Thus, this study aims to examine the motives that influence Netflix binge-watching b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…For example, Vaterlaus et al (2019) found that because students do not live with their parents, they have the freedom to marathon any shows as no one will stop them. Other motives for binge-watching include stress (Tefertiller & Maxwell, 2018), seeking to escape from academic tasks (Chan et al, 2022;Halfmann & Reinecke, 2021), fear of missing out (Susanno et al, 2019), impulsivity (Starosta et al, 2021), and enjoyment (Granow et al, 2018). Evidence has also shown that social anxiety (Sun & Chang, 2021) and the need to relax or unwind encourage students to binge-watch (Dixit et al, 2020;Tefertiller & Maxwell, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Vaterlaus et al (2019) found that because students do not live with their parents, they have the freedom to marathon any shows as no one will stop them. Other motives for binge-watching include stress (Tefertiller & Maxwell, 2018), seeking to escape from academic tasks (Chan et al, 2022;Halfmann & Reinecke, 2021), fear of missing out (Susanno et al, 2019), impulsivity (Starosta et al, 2021), and enjoyment (Granow et al, 2018). Evidence has also shown that social anxiety (Sun & Chang, 2021) and the need to relax or unwind encourage students to binge-watch (Dixit et al, 2020;Tefertiller & Maxwell, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Little research is available on samples from Malaysia, making the generalisation of past findings inappropriate for the Malaysian population as binge-watching patterns might differ across countries. Except for studies by Chan et al (2022), Mahmoud and Abdul Wahab (2021), Ramayan et al (2018), andTengku Mohd Azzman andAbdul Manaf (2022), there is almost no other research on bingewatching available. Even then, the scope of these studies either covers motives such as entertainment, social interaction, escapism, boredom or consequences, such as interpersonal communication or parasocial interaction.…”
Section: Introductionmentioning
confidence: 99%